Switching p53-dependent growth arrest to apoptosis via the inhibition of DNA damage-activated kinases - Hublarova, Pavla; Greplova, Kristina; Holcakova, Jitka; Vojtesek, Borivoj; Hrstka, Roman (Cellular & molecular biology letters, 2010)
Cisplatin and doxorubicin are widely used anticancer drugs that cause DNA damage, which activates the ATM-Chk2-p53 pathway in cancer cells. This activation leads to cell cycle block or apoptosis, depending on the nature of the DNA damage. In an attempt to enhance the effects of these agents, we inhibited ATM/ATR and Chk2, which are known upstream regulators of p53. The cancer cell lines A2780 and ARN8, bearing the wild-type p53 protein, were used to study changes in p53 activation and trans-activation. Our results suggest that the G(1)-checkpoint, normally activated by DNA damage, is functionally overcome by the action of kinase inhibitors that sensitize cells to apoptosis. Both inhibitors show these effects, albeit with variable intensity in different cell lines, which is promising for other studies and theoretically for use in clinical practice.
Keywords: nádorový supresorový protein p53; signální transdukce; nádorové buněčné linie; DNA Damage; DNA-Binding Proteins; Doxorubicin; checkpoint kinasa 2; apoptóza; průtoková cytometrie; Protein Kinase Inhibitors; poškození DNA; down regulace; ATM protein; Cisplatin; protein-serin-threoninkinasy; cisplatina; Signal Transduction; Checkpoint Kinase 2; Tumor Suppressor Protein p53; Cell Line, Tumor; Antineoplastic Agents; Cell Cycle Proteins; Down-Regulation; Resting Phase, Cell Cycle; G0 fáze; Flow Cytometry; Protein Serine-Threonine Kinases; proteiny buněčného cyklu; doxorubicin; nádorové supresorové proteiny; protinádorové látky; Humans; Tumor Suppressor Proteins; DNA vazebné proteiny; Ataxia Telangiectasia Mutated Proteins; inhibitory proteinkinas; lidé; Apoptosis